Bacterial Contamination of Contact Lenses Among Some Female Students and Employee of College of Education-Ibn AIÂ Haitham, University of Baghdad - Ibrahim, I. A-J; A L- Hadaria, S. A. M.; Fayidh, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
During the last few yt:ars, au increase :n ut ilization of contact ienses (both cosmetic and correction of refractive errors lenses) was noticed among yotmg females, with an increase in eye infections. The present i nvocation was carried out to demonstrate the percentage of bacter ial contamination of both the preservation fluid and lens oonlainers. FiftyÂ two contact lenses users among female students and em I ployees of college of Education-Ibn Al- Haitham were surveyed. Data were obtained on methodof usage and results of microbial examination. The following points were reached. 1- Gram-negative bacteria were the most common ones, especially Pseudomonas aero!inosa with 38.9%1 of the total isolates. 2- Results of sensitivity tests for antibiotics revealed that ofloxacin, ciprotloxacin. chlorampht:nicol , gentamycin and tobramycin were effective against isolated bacteria from containers and preservative fluids of content lenses. 3- Improper and non hygienic measure::; were employed especially in connection with keepi ng the preservative fluid and the containers tidy.